Effectiveness of a Brief Psychotherapeutic Intervention for Employees With Psychosomatic and Psychosocial Complaints—Pilot Study of a Consultation Off the Workplace - Allwang, Christine; Marten-Mittag, Birgitt; Dinkel, Andreas; Mauss, Daniel; Lahmann, Claas (Frontiers in Psychiatry, 2020)
Employees' mental health impairments are a leading reason for sickness-leave and early retirement. This is why a large number of different intervention programmes have evolved in recent years with the aim of counteracting this development. Our study evaluates a short-term cognitive-behavioral psychotherapeutic intervention off the workplace. We investigated improvement of mental and physical health in psychologically strained employees of a white collar company. Depressive symptoms (PHQ-9), anxiety symptoms (GAD-7), somatic symptoms (PHQ-15), and perceived stress (PSQ-20) were assessed at the beginning and after the intervention. Patient satisfaction (recommendation - likeliness) was also measured after the intervention. In a second step we have looked at potential determinants of therapy outcome. Changes in the symptom measures were assessed using t-tests, MANOVA and Chi²-tests. Cohen's d was computed as effect size measure. 127 participants completed the assessment before, and 66 participants post intervention. Mean age of the participants was 44.6 (SD = 9.8) years, 54% were men. 89.7 % of the patients attended one to five sessions. Depressive, anxiety, somatic symptoms, and perceived stress significantly declined from baseline to end of intervention. Effect sizes ranged from d= 0.49 (perceived stress) to d= 0.72 (depressive symptoms). Moreover, 93% of the patients stated that they were satisfied with the intervention and would recommend it to a friend. Previous uptake of psychiatric/psychotherapeutic treatment moderated the effect of the intervention on depressive symptoms, i.e. patients without previous experience showed a stronger reduction in symptoms of depression. The results tentatively suggest that the intervention is effective in reducing a broad range of psychological symptoms. Future research could investigate preferences and different outcomes of on-site and off-site work place interventions.